PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI DAN PENERAPAN SISTEM PENGENDALIAN INTERN PEMERINTAH TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN HALMAHERA UTARA - Mene, Restika Eklesia; Karamoy, Herman; Warongan, Jessy D.L (Universitas Sam Ratulangi, 2018)
Autonomous region demanded the Government Areas to provide the best service to the community. One form of such services is to provide financial information that is transparent and accountable. Accountability can be realized through local government financial reports are reliable in order to be trusted by users. The presence of finance report audit results areas that still require refinement exhortations continuously. Based on the Government Regulation Number 71 Year 2010, the quality of the financial report of the Central Government and regions must meet the qualitative characteristics, namely: relavan, reliably, understandable and comparable. This research aims to know the influence of the utilization of information technology and systems of internal control of financial reporting to the quality of government local government North Halmahera Regency as the sample. This research uses a quantitative approach, using primary data, the data collection was done by disseminating a questionnaire to all employees on the employees of the financial manager of the 28 units of Work Device area (SKPD) North Halmahera Regency by the number of respondents 60 people. Data analysis using the method of multiple regression analysis statistics. The results of hypothesis testing showed that the utilization of information technology and systems of internal control of the Government a positive and significant effect of the quality of the financial report of the local Government District of North Halmahera.Keywords: quality of the financial report of the Government of the region, the utilization of information technology and Government internal control Systems